A Unified Method for MSP Synthesis of Planar Four-Bar Function Generators. - Hernandez, Manuel V. (Philippine Engineering Journal)
A review of the synthesis of planar four bar function generators results in a more unified approach to the problem. The question of number of parameters available for synthesis vis-a-vis the number of synthesis equations is reconciled. Furthermore, the parameters used for synthesis are simply the coordinates of the vectors that define the mechanism. The method developed gives every explicit equations in these parameters and with slight modifications and derivations become applicable for higher order synthesis. Thus, the method is generalized for multiply-separated-position (MSP) synthesis of planar 4-bar function generators.